A study about creating sense of place for mosque compound - 298281 Hairul Hazar Midon (Skudai : Universiti Teknologi Malaysia, 2006)
Topical Study (Sarjana Muda Senibina Landskap) - Universiti Teknologi Malaysia, 2006